The Potential Benefits and Adverse Effects of Phytic Acid Supplement in Streptozotocin-Induced Diabetic Rats - F. O. Omoruyi; A. Budiaman; Y. Eng; F. E. Olumese; J. L. Hoesel; A. Ejilemele; A. O. Okorodudu (Hindawi Limited, 2013)
In this study, the effect of phytic acid supplement on streptozotocin-induced diabetic rats was investigated. Diabetic rats were fed rodent chow with or without phytic acid supplementation for thirty days. Blood and organ samples were collected for assays. The average food intake was the highest and the body weight gain was the lowest in the group fed phytic acid supplement compared to the diabetic and normal control groups. There was a downward trend in intestinal amylase activity in the group fed phytic acid supplement compared to the other groups. The spike in random blood glucose was the lowest in the same group. We noted reduced serum triglycerides and increased total cholesterol and HDL cholesterol levels in the group fed phytic acid supplement. Serum alkaline phosphatase and alanine amino transferase activities were significantly (P<0.05) increased by phytic acid supplementation. Systemic IL-1β level was significantly (P<0.05) elevated in the diabetic control and supplement treated groups. The liver lipogenic enzyme activities were not significantly altered among the groups. These results suggest that phytic acid supplementation may be beneficial in the management of diabetes mellitus. The observed adverse effect on the liver may be due to the combined effect of streptozotocin-induced diabetes and phytic acid supplementation.